The place of fixed antihypertensive drugs in modern therapy of arterial hypertension - Tatiana V. Pinchuk (IP Morozov P.V., 2021)
The article provides information on modern approaches to the treatment of arterial hypertension. The historical information about therapy with combined antihypertensive drugs is given. Based on data from multicenter clinical trials, the article provides evidence of the benefits of dual and triple fixed drug combinations. Combinations of 1-adrenoreceptor antagonist bisoprolol and the dihydropyridine-type calcium channel blocker amlodipine are considered. The article highlights the advantages of each of the drugs, as well as their combination. It shows the benefits of a fixed combination of low and medium doses compared to high-dose monotherapy, such as efficacy in achieving target blood pressure, preventing cardiovascular events, increasing adherence to treatment, safety and development of side effects. It provides the evidence base for the effectiveness of a triple fixed combination of renin-angiotensin-aldosterone system blockers with calcium channel blockers and diuretics in achieving target blood pressure compared to a double fixed combination of members of these drug classes, which is due to additive effects. The safety and tolerability profiles were found to be more effective with triple therapy compared with dual therapy, which is also supported by studies.